RESERVOIR CHARACTERISTICS AND 2D-CONNECTIVITY MODELING OF NEOGENE SILICICLASTIC SHALLOW-MARINE SUCCESSIONS OF SARAWAK AND SABAH, MALAYSIA - SIDDIQUI, NUMAIR AHMED (2016)
Sedimentological characteristics and pnmary depositional architecture of siliciclastic shallow-marine reservoirs in terms of reservoir heterogeneities and connectivity can improve the understanding of subsurface reservoir quality. Traditional datasets used in reservoir modeling (i.e. seismic and well data) cater a detenninistic architectural framework with detailed facies and petrophysical description only at discrete locations.